Upaya Penanaman Nilai Karakter Dalam Pembelajaran Musik Di SMP Negeri 18 Padang - Sari Rahmadany; Yuliasma Yuliasma (SENDRATASIK UNP, 2021)
This research aims to find out and describe the efforts of planting character values in music art learning at SMP N 18 Padang. This type of research is qualitative research with descriptive methods. The research object is grade VII-1 students and cultural arts teachers of SMP Negeri 18 Padang. The instruments in this study are the researchers themselves and the researchers assisted with supporting instruments such as stationery, mobile phones, and laptops. Research data collection techniques are interviews, observations and documentation. And the steps to analysis the data are data reduction, data collection, verification and conclusion. The results showed that in music learning ensembles the student's confidence character improved judging by the effect of his-confidence character namely, disciplined, creative, independent, responsible and evidenced by student indicators in collecting tasks on time, students diligently asking questions, answering and expressing opinions on the learning process, students doing their own tasks without imitating others, and taking group exercises. The teacher's efforts in instilling character values are appropriate enough to see some points of mulyasa theory that researchers make teacher benchmarks in an effort to instill character values, among others by giving opportunities to students, instilling moral values in learning, monitoring student work, motivating students and using varied media. The efforts that teachers make to cultivate character values through approaches to students and familiarize the character values that are expected according to the competency standards of graduates in daily life.